Evaluasi Kapasitas Ruang Parkir Universitas Musamus Merauke - Dina Pasa Lolo; Muh. Akbar; Silva Keiza Sahelangi; Dina Limbong Pamuttu; Hairulla; Mochammad Qomaruddin (Universitas Veteran Bangun Nusantara, 2025)
Musamus University is the only state university in South Papua Province. This campus provides parking spaces in various locations such as in the Faculty of Economics and Law, Deanery and Rectorate areas, but vehicles still often pile up. This research aims to determine the parking capacity of Musamus University. The research method is based on the 1998 Director General of Land Transportation's Technical Guidelines for the Implementation of Parking Facilities. The data collected is the number of incoming vehicles, the number of outgoing vehicles and the duration of the vehicle to find the value of the parking lot capacity. The results of the study at 3 points of the location of the motorcycle parking area of the Faculty of Economics and Law, the Deanery, and the Rectorate have a parking area of 216 m², 78 m², and 51 m², with a parking area requirement of 1,479 m², 289 m², and 231 m², then additional motorcycle parking areas are still needed, namely 1,263 m², 211 m², 180 m². In the car parking area of the Faculty of Economics and Law, the Deanery, and the Rectorate have a land area of 69 m², 80.5 m², and 57.5 m², a car parking area of 104 m², 173 m², and 173 m² is needed, so there is still a shortage of areas of 35 m², 92.5 m², and 115.5 m². The Faculty of Economics and Law's motorcycle prediction for the next 5 years is 312 SRP and cars 6 SRP.